Reforming Ethical Policing in Indonesia: Legal Protection for Conscientious Objection and the Duty to Disobey Unlawful Orders - Riphat, Mohammad Fattah; Widagdo, Setyo; Djatmika, Prija; Madjid, Abdul; Risyawan, Alief (Jambe Law Journal, 2025)
In the context of police institutions in Indonesia, members of the police force are often faced with a dilemma when receiving orders from superiors that have the potential to violate the law. On the one hand, there is an obligation to uphold the law and protect human rights. The conflict raises legal questions about the extent to which police officers in Indonesia are protected when they refuse or disobey unlawful orders, based on the principles of the right to conscientious objection and the duty to disobey. This study uses normative legal research and comparative doctrinal analysis to examine the conceptual underpinnings of these principles and evaluate institutional practice. Through an analysis of international legal instruments, national regulations, relevant case studies, and selected comparative materials, this article concludes that these two principles are an integral part of the development of a democratic, accountable, and human rights-oriented police institution in Indonesia, and therefore deserve comprehensive legal protection.